2008
DOI: 10.1136/jme.2007.021097
|View full text |Cite
|
Sign up to set email alerts
|

Lives in a chiaroscuro. Should we suspend the puberty of children with gender identity disorder?

Abstract: Transgender children who are not treated for their condition are at high risk of violence and suicide. As a matter of survival, many are willing to take whatever help is available, even if this is offered by illegal sources, and this often traps them into the juvenile criminal system and exposes them to various threats. Endocrinology offers a revolutionary instrument to help children/adolescents with gender identity disorder: suspension of puberty. Suspension of puberty raises many ethical issues, and experts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 13 publications
0
35
0
2
Order By: Relevance
“…GnRHa is now used to suppress puberty in adolescents with gender dysphoria and contemplating cross-hormone treatment and later genital surgery (25). Current controversies centre on whether such treatment should be instigated at an early Tanner stage or when puberty is almost complete (26). The following section concentrates solely on the application of GnRHa treatment in the management of precocious puberty.…”
Section: Precocious Puberty: Assessmentmentioning
confidence: 99%
“…GnRHa is now used to suppress puberty in adolescents with gender dysphoria and contemplating cross-hormone treatment and later genital surgery (25). Current controversies centre on whether such treatment should be instigated at an early Tanner stage or when puberty is almost complete (26). The following section concentrates solely on the application of GnRHa treatment in the management of precocious puberty.…”
Section: Precocious Puberty: Assessmentmentioning
confidence: 99%
“…Although medical treatment and health risks 63 in gender dysphoric adults are well defined and have been the object of more extended research in clinical settings [57][58][59] , the treatment strategy for young persons has received little attention in clinical research settings and is still debated 56 .…”
Section: [H1]balancing Observation and Interventionmentioning
confidence: 99%
“…Accordingly, undergoing the pubertal development of their biological sex could increase the 9 distress already associated with the condition, with serious risks for the individual's psychological well-being 56 . As studies have indicated that cross-sex hormonal treatment improves well-being in adults with gender dysphoria [57][58][59] , research has begun to focus on the effects of puberty suppression on quality of life in prepubertal and adolescent individuals with gender dysphoria, indicating that this early intervention could improve their psychosocial functioning and well-being [40][41][42] .…”
mentioning
confidence: 99%
“…Pour certains auteurs, ces traitements peuvent ainsi aider à réduire le taux de suicide qui est particulièrement élevé dans cette population [10]. Un autre argument soutenant le caractère bienfaisant psychologiquement de ces traitements est que cette méthode permet au mineur d'avoir plus de temps pour réfléchir à son identité sexuelle, sans faire l'expé-rience de vivre dans un corps perçu comme « étranger » ( [6], p. 580). Le troisième objectif de la transition sexuelle médicalement assistée est de réduire le harcèlement du patient par autrui : le passing permet au patient de cacher son sexe physiologique d'origine et donc d'évi-ter des situations où la dissonance (subjectivement perçue) entre le comportement genré et l'apparence physique provoquerait du harcè-lement ( [1], p. 340).…”
Section: La Transition Sexuelle Médicalement Assistéeunclassified
“…réponse médicale à un problème social, mais bien une réponse médi-cale à un problème médical [6]. À ces interprétations de la sexualité s'ajoute un mouvement de plus en plus répandu : la « dé-pathologisation » du transgénérisme.…”
unclassified